2008
DOI: 10.2320/matertrans.ma200803
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Study of Eutectic Structure in Nb-Ti-X and Nb-Zr-X (X = Co, Ni) Hydrogen Permeation Alloys

Abstract: The morphology and crystallography of eutectic structures in several niobium-bearing hydrogen permeation alloys such as Nb

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is now under study and will be reported in due course. It should be noted that the crystallized Nb 20 Ti 40 Ni 40 melt-spun ribbon consists of the duplex structure with the cube-on-cube orientation relationship which is quite different from the eutectic structure with a fine lamellar morphology in the Nb 20 Ti 40 Ni 40 cast alloy [8][9][10].…”
Section: Resultsmentioning
confidence: 97%
“…This is now under study and will be reported in due course. It should be noted that the crystallized Nb 20 Ti 40 Ni 40 melt-spun ribbon consists of the duplex structure with the cube-on-cube orientation relationship which is quite different from the eutectic structure with a fine lamellar morphology in the Nb 20 Ti 40 Ni 40 cast alloy [8][9][10].…”
Section: Resultsmentioning
confidence: 97%
“…Unlike for the NbTiNi alloys, it was reported that two types of misfit dislocation exist in the as-cast NbTiCo alloy; they form a complex phase boundary structure. 39) It is considered that these difference of phase boundary structures affects hydrogen permeability in Nb TiCo alloys. For a practical use of NbTiCo and NbTiNi alloys as hydrogen permeable alloys, it is essential to analyze not only the volume fraction of the (Nb, Ti) phase and microstructural morphology but also detailed microstructure including phase boundary structure.…”
Section: Relationship Between Microstructural Changes and Hydrogen Pe...mentioning
confidence: 99%